Evaluation of the Association between Programmed Cell Death-1 Gene Polymorphisms and Hepatocellular Carcinoma Susceptibility in Turkish Subjects. A Pilot Study - EREN, FATİH; GÜNDÜZ, FEYZA (MEDICAL UNIV PRESS, 2020)
Background & Aims: Programmed cell death-1 (PD-1) has a vital role in regulating T-cell function, and immune escape mechanism of cancer cells. It was shown that there could be a relationship between single nucleotide polymorphisms (SNPs) in the PD-I gene and susceptibility to hepatocellular carcinoma (MCC) based on various studies. We aimed to investigate the role of three SNPs within the PD-1 gene in susceptibility to HCC in the Turkish population. Methods: Single nucleotide polymorphisms of PD-1.1, 1.5, and 1.6 were genotyped by using TaqMan Allelic Discrimination Assays in blood samples of 137 HCC and 136 control subjects, matched for age and gender. The genotype, allele and haplotype frequencies were compared in HCC and control groups using logistic regression analysis. Results: Genotype distributions of PD-1.1, PD-1.5 and PD-1.6 SNPs were in Hardy-Weinberg equilibrium. No significant difference was observed in the genotype distribution of PD-I.1, PD-1.5 and PD-1.6 polymorphisms among gender and age-matched HCC (M/F: 96/41; mean age: 61.4 +/- 11.7 years) and control group (M/F: 94/42; mean age: 61.4 +/- 10.1). In the haplotype analysis of P1)-1.1/PD-1.5/PD-1.6, no significant difference was found among HCC and control group adjusted for sex and age (all p values>0.1). Conclusion: Our findings, firstly reporting the association of PD-1.5 polymorphism with I ICC, and PD-I.1 and PD-1.6 with HCC in the Turkish population, suggest that PD-1 polymorphisms are not predisposing factors for HCC development. Future studies with larger sample sizes and different ethnic populations are required to validate our findings.
Keywords: hepatocellular carcinoma; programmed cell death-1; single nucleotide polymorphisms; susceptibility; DEATH-1 GENE; LIGAND 1; EXPRESSION; PD-1; PROGRESSION; POPULATION; CANCER; PD1